ASSESSMENT OF THE SPATIAL APPROPRIATENESS OF THE FUTURE URBANIZATION OF THE CITY OF (AIN BEIDA, ALGERIA) USING GEOGRAPHIC INFORMATION SYSTEMS, THE ANALYTICAL HIERARCHY PROCESS, AND THE DELPHI METHOD - Amina Merakchi; Djamel Alkama; Khalid Zaouia (International Journal of Innovative Technologies in Social Science, 2024)
Spatial adequacy evaluation is a valuable tool for planning land use strategies. It provides planners with data and outcomes that can help them make informed decisions to ensure effective and secure utilization of land in future urbanization processes. The objective of this study is to analyze the urbanization patterns in the city of Ain El Beida to determine the most appropriate areas for urban development. The aim is to create self-sustaining growth centers that effectively support the city, while also helping decision-makers address current expansions and protect agricultural lands. The study utilized spatial analysis methodology to evaluate and map the suitability of expanding the city’s future space. It proposed an integration strategy that combined modern methods and techniques of the Delphi methodology to establish criteria for appropriate land use. The influence of these criteria will be analyzed spatially by administering a questionnaire to a sample of specialists in urban planning and city geography, followed by the application of spatial analyst techniques. The user’s text is straightforward and precise. within the GIS framework, integrated via the analytic hierarchy approach. The user’s text is straightforward and precise. To evaluate the suitability of the spatial location, to determine the significance of the factors influencing the expansion process based on their relative importance, to ensure that the desired goals are achieved in a way that reflects the priority of the decision-making criteria, and to identify the most favorable options for urban development in the study area. The findings indicated that the optimal locations for the urban growth of Ein El-Baida were determined to be 239.57 hectares, which accounts for 26.31 per cent of the entire land area under investigation. These areas are situated on the northern side of the city along National Road 80 (Ain Beida Presh) and on the western side along National Road 10 (Oum el-Bouaghi Ain Beida). These locations have been identified as the most suitable areas for spatial expansion due to their numerous incentives for urban attraction. Firstly, there is a considerable distance from the fertile and generously compensated agricultural areas, which offer unoccupied and level terrain, as well as its proximity to the central area of the pristine city of Ein. The study also determined that integrating GIS with hierarchy is crucial for constructing spatial models that accurately represent physical reality through mathematical means. This integration aids planners in selecting the most appropriate alternatives for urbanization and achieving comprehensive development of the city.